PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN GUDEG YU DJUM YOGYAKARTA JL. WIJILAN No. 31 KOTA YOGYAKARTA - Abdul Makbud; Ida bagus Nyoman; Bernadetta Diansepti Maharani (Jurnal Akuntansi Dan Manajemen, 2022)
This study was conducted to analyze the variables that affect customer satisfaction Gudeg Yu Djum Yogyakarta. The independent variables consist of Product Quality (X1), Service Quality (X2), and Price Perception (X3). The dependent variable is Customer Satisfaction (Y). The sample taken is the customer Gudeg Yu Djum Jl. Wijilan No.31 Yogyakarta who bought and consumed Gudeg Yu Djum products Jl. Wijilan No.31 Yogyakarta. The number of samples taken amounted to 100 respondents using a purposive sampling technique. The analytical tool used is SPSS25. Based on the results of the analysis and discussion using multiple regression analysis shows that product quality, service quality, and price perception have a significant positive effect on customer satisfaction. Partially, product quality has a negative significant effect on customer satisfaction. Partially, service quality has a positive significant effect on customer satisfaction. Partially, price perception has a significant negative effect on customer satisfaction, while simultaneously product quality, service quality, and price perception have a significant positive effect on customer satisfaction.